PENGEMBANGAN PEMBALUT KAIN YANG RAMAH LINGKUNGAN SEBAGAI ALTERNATIF PILIHAN UNTUK KESEHATAN REPRODUKSI PEREMPUAN - diiniyati, diniyati; Kusmaryati, Pauline (Politeknik Kesehatan Kemenkes Bengkulu, 2020)
This research is about developing cloth pads using diadora cloth, fleece shirts and milky parachute cloth. This research was carried out at the Jambi Ministry of Health Poltekkes Department of Midwifery in 2019. This study aims to produce a product that is comfortable to wear on any occasion and does not leak when used during menstruation. Development carried out through the 3-D Model has stages including: defining, designing, developing. The product of this research is environmental friendly fabric. This bandage was tested limited to Jambi Health Polytechnic students and was field tested. The subjects in this study were 33 students from the Polytechnic of the Ministry of Health Jambi Department of Midwifery conducted in January to November 2019 Student trials with average results in answering instruments reached 90% so as to produce environmentally friendly fabric pads. For other researchers. Researchers suggest that the cloth pads be developed again by being trialled at several schools to get more diverse results and the use of these cloth pads in accordance with the results that have been developed. There are those who want to develop further so that this product is more perfect. It is recommended that researchers give opportunities to develop cloth products widely